Application of a Maintenance Management Model Based on LEAN TPM to Increase OEE in Canning SMEs - Soto Loncharich, Diego Miguel (2023)
Regardless of the factory type, the performance of machinery is an important factor to be competitive. To ensure optimal equipment performance, many companies focus on establishing continuous improvement programs. This is the reason why there are methods, with the final purpose to increase the disponibility and operation, additionally, it also produces regulations of order, because it helps to reduce unused times, as is the case of 5S. Likewise, efficiency is also measured through the OEE maintenance KPI (equipment effectiveness) averaging a moderation towards the implementation of management methods. This article presents the implementation of two of the pillars: the TPM (preventive maintenance and autonomous maintenance) and 5s. Further, the most relevant contribution after the application of these methods, is the performance increase on the OEE. For this case study, after the simulation, the result is 6.85%, a plus than the current situation, where the performance is 6.45%.